Análise comparativa da área dos retropreparos obtidos com pontas ultrassônicas diamantadas convencionais e pontas CVD: estudo em microscopia eletrônica de varredura - Paiva, Fernanda Garcia (2009)
The present work aimed to analyse dentinal cut and describe the appearance of retrocavities margins obtained with three different types of diamond-coated retrotips. Two of the tested retrotips, Trinity and Satelec, have regular diamond-coat, whereas the third type exhibits CVD-coat. The CVD surface is the result of a traditional technology manufactoring innovation, in which a policrystalin diamond film is deposited on the shaft . This property guaranttes a vigorous cutting ability sustainded for repeated use, without loss of its efficiency. Thirty two extracted human teeth were analysed through epoxi resin replicas.and scanning electron microscopy in two different stages: after apicectomy and after preparation with ultrasonic tips. The images were captured and sent to Image Tool® software for measurement. of the canal/retrocavity of the two stages. Data obtained in both experimental stages were compared to dentinal cut extent analysis. To margin scores, visual analysis of SEM images after apical preparation was used. Statistical analyses were based in t Student test, ANOVA and qui-square with level of significance of 95%. Trinity tips produced more extensive dentinal cut, and all specimens showed smooth margins. Satelec tips produced more conservative apical cavities preparations and high frequency of retrocavities with smooth margins. The CVD tips showed dentinal cut extent comparable to that observed with Trinity tips and the highest incidence of irregular margins. Satelec tips produced less extensive dentinal cut and Trinity tips produced most regular retrocavities.